A robust AFM-based method for locally measuring the elasticity of samples - Bubendorf, Alexandre; Walheim, Stefan; Schimmel, Thomas; Meyer, Ernst (Beilstein Journal of Nanotechnology, 2018)
Investigation of the local sample elasticity is of high importance in many scientific domains. In 2014, Herruzo et al. published a new method based on frequency-modulation atomic force microscopy to locally determine the elasticity of samples (Nat. Commun. 2014, 5, 3126). This method gives evidence for the linearity of the relation between the frequency shift of the cantilever first flexural mode Δf1 and the square of the frequency shift of the second flexural mode Δf22. In the present work, we showed that a similar linear relation exists when measuring in contact mode with a certain load FN and propose a new method for determining the elastic modulus of samples from this relation. The measurements were performed in non-dry air at ambient temperature on three different polymers (polystyrene, polypropylene and linear low-density polyethylene) and a self-assembled monolayer of 1H,1H,2H,2H-perfluorodecyltrichlorosilane (FDTS) on a silicon oxide substrate perforated with circular holes prepared by polymer blend lithography. For all samples the relation was evidenced by recording Δf1, Δf2 and FN as a function of the Z-displacement curves of the piezoelectric scanner. The occurence of a plastic deformation followed by an elastic deformation is shown and explained. The necessary load FN for measuring in the elastic domain was assessed for each sample, used for mapping the frequency shifts Δf1 and Δf2 and for determining the elastic modulus from Δf22/Δf1. The method was used to give an estimate of the Young’s modulus of the FDTS thin film.
Keywords: atomic force microscopy; contact resonances; elastic modulus; 1H,1H,2H,2H-perfluorodecyltrichlorosilane (FDTS); polymers; Young’s modulus

Life at the Nanoscale: Atomic Force Microscopy of Live Cells - Kasas, S.; Dietler, G. (Probing the Nanomechanical Properties of Viruses, Cells and Cellular Structures, 2011)

(untitled) - Dai, S.; Zhao, J.; He, M.-r.; Wang, X.; Wan, J.; Shan, Z.; Zhu, J. (Nano Lett., 2015)

(untitled) - Lu, H.; Meng, X. (Sci. Rep., 2015)

(untitled) - Binnig, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Tamayo, J.; Garcia, R. (Appl. Phys. Lett., 1997)

(untitled) - Hurley, D. C.; Turner, J. A. (J. Appl. Phys., 2007)

(untitled) - Herruzo, E. T.; Perrino, A. P.; Garcia, R. (Nat. Commun., 2014)

Elasticity of Polymers Investigated by Atomic Force Microscopy - Bubendorf, A. (University of Basel, 2015)

Applied Scanning Probe Methods II - Rabe, U. (Atomic Force Acoustic Microscopy, 2006)

(untitled) - Rabe, U.; Turner, J.; Arnold, W. (Appl. Phys. A, 1998)

(untitled) - Rabe, U.; Arnold, W. (Appl. Phys. Lett., 1994)

Ultrasonics - Rabe, U.; Amelio, S.; Kester, E.; Scherer, V.; Hirsekorn, S.; Arnold, W. (Quantitative determination of contact stiffness using atomic force acoustic microscopy, 2000)

(untitled) - Rabe, U.; Amelio, S.; Kopycinska, M.; Hirsekorn, S.; Kempf, M.; Göken, M.; Arnold, W. (Surf. Interface Anal., 2002)

Acoustic Scanning Probe Microscopy - Rabe, U.; Kopycinska-Müller, M.; Hirsekorn, S. (Atomic Force Acoustic Microscopy, 2012)

(untitled) - Lozano, J. R.; Garcia, R. (Phys. Rev. Lett., 2008)

(untitled) - Garcia, R.; Herruzo, E. T. (Nat. Nanotechnol., 2012)

(untitled) - Rodriguez, T. R.; Garcia, R. (Appl. Phys. Lett., 2004)

(untitled) - Proksch, R. (Appl. Phys. Lett., 2006)

(untitled) - Martínez, N. F.; Lozano, J. R.; Herruzo, E. T.; Garcia, F.; Richter, C.; Sulzbach, T.; Garcia, R. (Appl. Phys. Lett., 2008)

(untitled) - Herruzo, E. T.; Garcia, R. (Beilstein J. Nanotechnol., 2012)

(untitled) - Garcia, R.; Proksch, R. (Eur. Polym. J., 2013)

Friction and Rheology on the Nanometer Scale - Meyer, E.; Gyalog, T.; Overney, R. M.; Dransfeld, K. (World Scientific Publishing Co Pte Ltd, 1998)

(untitled) - Rast, S.; Wattinger, C.; Gysin, U.; Meyer, E. (Rev. Sci. Instrum., 2000)

(untitled) - Huang, C.; Moosmann, M.; Jin, J.; Heiler, T.; Walheim, S.; Schimmel, T. (Beilstein J. Nanotechnol., 2012)

Springer Handbook of Condensed Matter and Materials Data - Lechner, M. D. (Polymers, 2005)

Materials Data Book (Cambridge University Engineering Department, 2003)

(untitled) - Howald, L.; Lüthi, R.; Meyer, E.; Güntherodt, H.-J. (J. Phys.: Condens. Matter, 1994)